2008
DOI: 10.1111/j.1740-1461.2008.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

The Health Cost of Civil‐Law Problems: Further Evidence of Links Between Civil‐Law Problems and Morbidity, and the Consequential Use of Health Services

Abstract: There is considerable evidence of links between social and health problems. Some of these links involve social problems that can be addressed through civil legal process, and may be described as civil‐law problems. Various initiatives have been implemented around the world to link health and legal advice services to promote better health and justice outcomes. This study examines the links between civil‐law problems and morbidity. It uses new data to replicate an earlier analysis of these links, then builds on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Kempson, ; Department for Trade and Industry, ; Kempson et al ., ). There was also evidence that people with a long‐term illness or disability were more likely to experience unmanageable debt and financial difficulty, once one accounts respondent age, consistent with previous research showing an interaction between age and health in the experience of civil justice problems more generally (Pleasence et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Kempson, ; Department for Trade and Industry, ; Kempson et al ., ). There was also evidence that people with a long‐term illness or disability were more likely to experience unmanageable debt and financial difficulty, once one accounts respondent age, consistent with previous research showing an interaction between age and health in the experience of civil justice problems more generally (Pleasence et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Crucially, our research suggests that the relationship between health and legal needs is complex and multilayered. Although the interlinkages between health and legal problems has been well documented (e.g., Balmer et al 2010;Pleasence et al 2008a), and research has demonstrated the benefits from coordinated provision of health and legal services (Cohen et al 2010;Lawton et al 2010), our research reveals some additional challenges to effective provision. Notable among these is the need for delivery and service structures to take account of the ways preexisting medical conditions, or treatment for them, interfere with problem detection.…”
Section: Multiple Legal Problems and Advice Seekingmentioning
confidence: 73%
“…; Pleasence et al. ), and research has demonstrated the benefits from coordinated provision of health and legal services (Cohen et al. ; Lawton et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The English and Welsh Civil and Social Justice Survey (CSJS) used in the present study has been designed to capture a broad range of such rights problems in eighteen areas (see Table 1, which also provides some examples). Previous research has highlighted the relationship between morbidity and the experience of social problems involving legal rights (‘rights problems’) (Pleasence et al . 2004a, 2008), a relationship observed in a number of countries (e.g.…”
Section: Introductionmentioning
confidence: 99%